GRAMMAR ERROR LEVELS IN ENGLISH FACEBOOK ALUMNI POSTING - Muzdalifah, Indah; Handayani, Susi; Musfawatit, Musfawatit (Universitas PGRI Sumatera Barat, 2019)
Facebook is a sharing tool in the form of social networks. One way to share is by making a post or uploading a photo added by a caption. This study analyzes errors that often occur in facebook posts by internet users who have a background in English or English Literature Education. Therefore, this study aims to describe the level of error especially in the field of the grammatical structure using the automatic grammar checker application. This research method uses descriptive qualitative research methods that explain the level of grammar errors in one's facebook posts. The results of this study were 42 samples taken that 78.5% of posts in English on Facebook were still problematic in the grammatical structure.